Effects of Ramadan fasting on biochemical and anthropometric parameters in physically active men - Trabelsi, K.; Abed, K. E.; Trepanowski, J. F.; Stannard, S. R.; Ghlissi, Z.; Ghozzi, H.; Masmoudi, L.; Hakim, A.; Jammoussi, K. (Asian Journal of Sports Medicine, 2011)
Purpose: The aim of this study was to assess the effects of Ramadan fasting on several biochemical and anthropometric parameters in physically active men by comparing fasters and nonfasters before, during, and after Ramadan. Methods: Eighteen physically active men (10 fasters and 8 nonfasters) participated in this study. Subjects visited the laboratory for a total of four sessions on the following occasions: three days before Ramadan (Bef-R), the 15th day of Ramadan (Mid-R), the 29th day of Ramadan (End-R), and 21 days after Ramadan (Post-R). During each session, subjects underwent anthropometric measurements, completed a dietary questionnaire and provided a fasting blood sample. Results: Body weight and body fat percentage decreased in fasters by 1.9% (P<0.001) and 6.2% (P=0.003), respectively, but increased in nonfasters by 2.2% (P<0.001) and 10.2% (P=0.001), respectively, from Bef-R to End-R. Fasters' hematocrit and hemoglobin increased by 5.3% (P<0.001) and 6.3% (P=0.01), respectively, from Bef-R to End-R, while neither of these parameters changed in nonfasters. Fasters experienced an increase in the following parameters from Bef-R to End-R: urea (8.7%; P<0.001), creatinine (7.5%; P<0.001), uric acid (12.7%; P<0.001), serum sodium (1.9%; P<0.001), serum chloride (2.6%; P<0.001) and high-density lipoprotein cholesterol (27.3%; P<0.001). Of these parameters, only creatinine increased (4.4%; P=0.01) in nonfasters. Conclusions: We conclude that Ramadan fasting lowers body weight and body fat percentage and can elevate high-density lipoprotein cholesterol in physically active men. However, practicing aerobic exercise during a hot and humid Ramadan month can induce a state of dehydration marked by an increase in some renal function markers and serum electrolytes.